2002
DOI: 10.1067/mva.2002.123676
|View full text |Cite
|
Sign up to set email alerts
|

Response of plasma matrix metalloproteinase-9 to conventional abdominal aortic aneurysm repair or endovascular exclusion: Implications for endoleak

Abstract: Plasma MMP-9 levels remain elevated for as much as 3 months after conventional AAA repair, whereas successful endovascular exclusion of an AAA results in decreased plasma MMP-9 levels by 3 months. MMP-9 may have clinical value as an enzymatic marker for endoleak after endovascular AAA exclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
2
12

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(108 citation statements)
references
References 34 publications
4
90
2
12
Order By: Relevance
“…A parte la diagnostica strumentale, è possibile valutare il danno endoteliale con esami di laboratorio; negli ultimi anni si è andato affermando, nei pazienti che hanno subito l'impianto di un'endoprotesi in aorta, il dosaggio sierico delle MMPs, che vengono considerate come possibili markers di danno endoteliale [22,38].…”
Section: Valutazione Laboratoristica Del Danno Endotelialeunclassified
“…A parte la diagnostica strumentale, è possibile valutare il danno endoteliale con esami di laboratorio; negli ultimi anni si è andato affermando, nei pazienti che hanno subito l'impianto di un'endoprotesi in aorta, il dosaggio sierico delle MMPs, che vengono considerate come possibili markers di danno endoteliale [22,38].…”
Section: Valutazione Laboratoristica Del Danno Endotelialeunclassified
“…This could presumably be the reason why the circulating MMP-9 levels remained similar to the preoperative high levels, but with no increasing tendency. 39 Once again, in patients with successful exclusion (no endoleaks), the MMP-9 levels decreased significantly. 40 The association between the MMPs and the endoleakrelated pressurization of the sac could possibly be interpreted from the recent findings by Rahman et al, who studied the levels of MMPs in areas of low and high wall stress values in the AAA wall.…”
Section: Association Of Biomarkers With Hemodynamic Changesmentioning
confidence: 99%
“…37 A number of studies have reported the use of MMPs after EVAR as enzymatic markers for endoleak. [38][39][40] Sangiorgi et al reported a significant decrease in plasma MMP-3 and MMP-9 levels for 6 months after successful endovascular repair. On the contrary, an increase of MMP levels in the presence of endoleaks in seven patients was observed, which decreased significantly after successful treatment of these endoleaks.…”
Section: Association Of Biomarkers With Hemodynamic Changesmentioning
confidence: 99%
“…Indeed, patients with plasma levels of MMPs that did not return to basal levels were more prone to develop endoleaks and aneurysm expansion. However, MMPs appear to remain elevated for at least three months in open surgery while they return to baseline more rapidly following endovascular graft implantation [6]. Other markers of potential predictive value were tested for the detection of potential endoleak development following stent-graft treatment.…”
Section: Editorial Commentmentioning
confidence: 99%